Andrew Fyfe the elder (1752(4)–1824): Not all good anatomists are good teachers. Issue 4 (10th May 2012) - Shoja, Mohammadali M.; Mortazavi, Martin M.; Malakpour, Mehran; Loukas, Marios; Rozzelle, Curtis J.; Tubbs, R. Shane
Abstract The history of teaching anatomy in Scotland is rich. One Scottish anatomist who has received little attention, however, is Andrew Fyfe the elder. Unfortunately, very little is written on the life and contributions of this early anatomist. He is considered to have been a great anatomist of his day, but a poor teacher of anatomy. Herein, we review the life of this early anatomist whose works have been compared to those of well‐known Scottish anatomists such as the Monros and brothers John and Charles Bell. Clin. Anat. 2013. © 2012 Wiley Periodicals, Inc.